Profiling Transcriptional Regulation and Functional Roles of Schistosoma mansoni c-Jun N-Terminal Kinase - Gava, Sandra Grossi; Tavares, Naiara Clemente; Falcone, Franco Harald; Oliveira, Guilherme; Mourão, Marina Moraes (Frontiers in Genetics, 2019)
Mitogen-activated protein kinases (MAPKs) play a regulatory role and influence various biological activities, such as cell proliferation, differentiation, and survival. Our group has demonstrated through functional studies that Schistosoma mansoni c-Jun N-terminal kinase (SmJNK) MAPK is involved in the parasite’s development, reproduction, and survival. SmJNK can, therefore, be considered a potential target for the development of new drugs. Considering the importance of SmJNK in S. mansoni maturation, we aimed at understanding of SmJNK regulated signaling pathways in the parasite, correlating expression data with S. mansoni development. To better understand the role of SmJNK in S. mansoni intravertebrate host life stages, RNA interference knockdown was performed in adult worms and in schistosomula larval stage. SmJNK knocked-down in adult worms showed a decrease in oviposition and no significant alteration in their movement. RNASeq libraries of SmJNK knockdown schistosomula were sequenced. A total of 495 differentially expressed genes were observed in the SmJNK knockdown parasites, of which 373 were down-regulated and 122 up-regulated. Among the down-regulated genes, we found transcripts related to protein folding, purine nucleotide metabolism, the structural composition of ribosomes and cytoskeleton. Genes coding for proteins that bind to nucleic acids and proteins involved in the phagosome and spliceosome pathways were enriched. Additionally, we found that SmJNK and Smp38 MAPK signaling pathways converge regulating the expression of a large set of genes. C. elegans orthologous genes were enriched for genes related to sterility and oocyte maturation, corroborating the observed phenotype alteration. This work allowed an in-depth analysis of the SmJNK signaling pathway, elucidating gene targets of regulation and functional roles of this critical kinase for parasite maturation.